Human Rights and Forced Displacement of the Population (a Note about the Difficulties in the Case of Colombia) - Carballo Armas, Pedro (The Age of Human Rights Journal, 2014)
With just over three million displaced persons, Colombia has a huge number of internally displaced persons and, without any doubt, is one of the largest in the world, entrenched for decades. The armed conflict raging in their society, especially in rural areas where there is little institutional presence, has resulted in a constant struggle in those territories between the “guerrillas” and paramilitaries. The validity of this conflict helps explain the idea of the dispossession suffered and the consequent abandonment of territories by the population, making this sort of internal diaspora called internal displacement. The government response is far from optimal because usually massive displacement of communities has produced a new phenomenology in dispute in reception sites, within the country’s own borders: isolation and maladjustment; marginality (and consequent invisibility), confinement, and social conflict. This analysis aims to highlight the humanitarian crisis and human rights conflict that stems from forced displacement and government policies, and the need to establish an efficient database to know the situation of the displaced population. Also it redefines a minimum list of essential rights of conflict victims and the feasibility of a transitional justice process.